Manufacturing and technology management - Jhamb,L.C (Everest Pub. House, 2010)
Manufacturing and technology management / Jhamb,L.C.. -- Pune: Everest Pub. House, 2010 658.5 J61e12 12th ed. No. of Copies : 1